Repurposed Nrf2 activator dimethyl fumarate rescues muscle inflammation and fibrosis in an aggravated mdx mouse model of Duchenne muscular dystrophy - Stephanie Kourakis; Cara A. Timpani; Ryan M. Bagaric; Bo Qi; Benazir A. Ali; Rebecca Boyer; Guinevere Spiesberger; Nitika Kandhari; Xu Yan; Jujiao Kuang; Ankita Tulangekar; Judy B. de Haan; et al. (Redox Biology)
In inherited neuromuscular disease, Duchenne muscular dystrophy (DMD), glucocorticoids significantly slow disease progression yet impart side effects severe enough to preclude use in a significant proportion of patients. Extending our findings that acute treatment with FDA approved multiple sclerosis drug, dimethyl fumarate (DMF), rescues muscle pathology in juvenile mdx mice, we aimed to conduct tiered pre-clinical testing toward translation. To aggravate disease phenotype in adult mdx muscles that usually lack human equivalent muscle pathology, we used bi-weekly treadmill running for 4 weeks which increased plasma DMD biomarker, creatine kinase, by 2-fold and quadriceps fibrosis by ∼30 %. Using this model, we screened DMF for 5 weeks in a head-to-head comparison, and in combination, with standard-of-care prednisone (PRED), to model the most likely clinical trial scenario. We show comparable efficacy between DMF and PRED at reducing inflammation via NF-κB suppression and CD68+ macrophage infiltration. Moderate term DMF monotherapy had additional anti-fibrotic and anti-lipogenic effects on skeletal and cardiac muscle beyond those seen with PRED treatment, although combination therapy exacerbated fibrosis in quadriceps. Our study supports DMF as a repurposing candidate for DMD, especially for patients who cannot tolerate chronic glucocorticoid treatment. We also highlight the importance of evaluating combination therapy to identify potential off-target effects between emerging therapeutics and glucocorticoids towards better designed clinical trials.